Faktor-faktor yang mempengaruhi Return on Deposit (ROD) - Dwivana, Anisa; Eliyanora, Eliyanora; Sudirman, Josephine (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the factors influencing the Return on Deposit (ROD) of Islamic Commercial Banks in Indonesia during the period 2021–2024. The independent variables used include the Capital Adequacy Ratio (CAR), Operating Expenses to Operating Income (BOPO), Non-Performing Financing (NPF), Total Assets (Bank Size), Board of Directors, and Independent Commissioners. This research employs a quantitative approach with descriptive analysis and multiple linear regression using IBM SPSS Statistics 31. The sample consists of 11 Islamic Commercial Bank with a total of 44 observations. The results show that CAR, NPF, and Independent Commissioners significantly affect ROD, while BOPO, Total Assets, and the Board of Directors have no significant influence on ROD. The coefficient of determination (R²) of 42.7% indicates that the variation in ROD can be explained by this model. These findings are expected to provide insights for Islamic banks in strengthening capital management strategies, financing risk control, and the role of independent commissioners to enhance competitiveness and depositor confidence.